Quantitative study of the effect of professional stress on absenteeism, mediated by organizational engagement, among primary public school teachers - LAHLIMI, Youssef-karim (Revue Internationale des Sciences de Gestion, 2024)
The education sector is a vital pillar of social progress, shaping future leaders and responsible citizens. Teachers, as essential actors in this sector, have an invaluable role to play. Their impact extends far beyond the mere transmission of academic knowledge as they guide and shape young minds. However, it is important to recognize that teachers themselves are not immune to the challenges and pressures of the professional environment, particularly stress, which can hinder their well-being. In the face of these challenges, it is crucial to examine the relationship between work-related stress, organizational commitment, and absenteeism within educational institutions. A quantitative approach, such as the one used in this study with Smart PLS, allows for a systematic analysis and empirical validation of these relationships. The empirical survey was conducted with 134 teachers working in public primary schools in rural areas.The results highlight the significant impact of stress on organizational commitment, which acts as a mediator in the relationship between stress and absenteeism. This suggests that teachers’ commitment to their organization can influence how work- related stress affects their presence and well-being.